Effective Treatment of Depressive Disorders in Medical Clinics for Adolescents and Young Adults Living With HIV: A Controlled Trial. (1st January 2016) - Brown, Larry K.; Kennard, Betsy D.; Emslie, Graham J.; Mayes, Taryn L.; Whiteley, Laura B.; Bethel, James; Xu, Jiahong; Thornton, Sarah; Tanney, Mary R.; Hawkins, Linda A.; Garvie, Patricia A.; Subramaniam, Geetha A.; et al.
Abstract : Objective: Preliminary test of a manualized, measurement-guided treatment for depression for adolescents and young adults in care at 4 sites of the Adolescent Trials Network for HIV/AIDS Interventions. Design: The US sites were randomly assigned to either a 24-week, combination cognitive behavioral therapy and medication management algorithm (COMB) tailored for youth living with HIV (YLWH) or to treatment as usual (TAU). Methods: Youth at TAU sites had access to therapists and medication management as needed. COMB-site clinicians were trained in the manualized intervention and participated in supervision calls to monitor intervention fidelity. Results: Over the course of the study with 44 participants, those in COMB, compared with those in TAU, reported fewer depressive symptoms, P < 0.01 (as measured by the Quick Inventory for Depression symptoms) and were more likely to be in remission, P < 0.001 (65% vs. 10% at week 24, end of treatment, and 71% vs. 7% at week 48, final follow-up). A greater proportion of COMB participants received psychotherapy (95% vs. 45%, P < 0.001) and attended more sessions (12.6 vs. 5, P < 0.001) than those in TAU. Viral load decreased in both groups and was associated ( P < 0.05) with reduction in depressive symptoms. Conclusions: A 24-week manualized, measurement-guided psychotherapy and medication management algorithm tailored for YLWH was more effective in achieving and sustaining remission from depression than TAU at HIV care clinic sites. Given observed treatment efficacy, this structured combination treatment could be disseminated to medical clinics to successfully treat YLWH, who are at particular risk for depression. Abstract : Supplemental Digital Content is Available in the Text.